2016
DOI: 10.1038/onc.2016.169
|View full text |Cite
|
Sign up to set email alerts
|

Sos1 disruption impairs cellular proliferation and viability through an increase in mitochondrial oxidative stress in primary MEFs

Abstract: Using a 4-hydroxytamoxifen (4OHT)-inducible, conditional Sos1-null mutation, we analyzed wild-type (WT), single Sos1-KO, Sos2-KO and double Sos1/2 KO primary mouse embryonic fibroblasts (MEF) with an aim at evaluating the functional specificity or redundancy of the Sos1 and Sos2 alleles at the cellular level. The 4OHT-induced Sos1-KO and Sos1/2-DKO MEFs exhibited distinct flat morphology, enlarged cell perimeter and altered cytoskeletal organization that were not observed in the WT and Sos2-KO counterparts. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
53
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(66 citation statements)
references
References 65 publications
11
53
0
Order By: Relevance
“…1a, left panel). Western blot (WB) analysis confirmed the disappearance of the Sos1 and Sos2 proteins in skin of mice treated under these experimental conditions and confirmed our previous observations in MEFs (18), indicating that there are no compensatory changes of either Sos1 or Sos2 protein expression when the other form is absent (Fig. 1a, right panel).…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…1a, left panel). Western blot (WB) analysis confirmed the disappearance of the Sos1 and Sos2 proteins in skin of mice treated under these experimental conditions and confirmed our previous observations in MEFs (18), indicating that there are no compensatory changes of either Sos1 or Sos2 protein expression when the other form is absent (Fig. 1a, right panel).…”
Section: Resultssupporting
confidence: 89%
“…Consistently, our analyses under physiological conditions first documented the functional relevance of Sos1 (predominant) and Sos2 for normal skin cell proliferation, and our skin wound repair studies further demonstrated a reduction of cell proliferation and migration of fibroblasts to the wounded area in Sos1/2-DKO mice. Other reports have also demonstrated a significant blockade of migration in both Ras-and Sos-depleted MEFs after wounding (18,26).…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…The low recovery neutrophils number has severely restricted the experiments we could conduct; thus, direct assays of Ras activation were impractical. It has been shown previously, however, that in fibroblasts isolated from the same mouse strains, loss of SOS1/2 resulted in an almost complete blockade of EGF or PDGF‐stimulated Ras activation . In unprimed cells, fMLP‐stimulated ERK activation (Fig.…”
Section: Resultsmentioning
confidence: 67%